Development of Adventure-Based Educational Games to Improve Critical Thinking Skills and Interest in Learning - Regan Moro, Fabianus; Zamzam, Kenys Fadhilah (Pi: Mathematics Education Journal, 2025)
Games are widespread in society, not only among children but adults also play games. It is not uncommon for school-age children to play this game until late at night which of course interferes with their study time. In this study, the researcher developed an educational game called "Math Adventure".  This educational game makes students learn while playing because, on the one hand, students play but on the other hand it is also useful to provide education or lessons for students. The educational game "Math Adventure" developed by the researcher contains questions from the two-variable linear equation system material.  The game "Math Adventure" is a type of adventure game in a maze where the character will look for the correct answer in a box or room in a maze. There are 4 answers available and are spread across 4 different rooms. The game "Math Adventure" has gone through a validation process by two validators and has been tested on 5 students. In the validation process, the game "Math Adventure" was declared valid and worth testing. Based on the results of the students' responses after being tested the game "Math Adventure" received a good response from the students.  The game "Math Adventure" can be used as an alternative for teachers to improve students' critical thinking skills and students' interest in learning in mathematics lessons.